Periodontitis induced by Porphyromonas gingivalis drives impaired glucose metabolism in mice - Kang, Ni; Zhang, Yong; Xue, Fei; Duan, Jinyu; Chen, Fan; Cai, Yu; Luan, Qingxian (Frontiers in Cellular and Infection Microbiology, 2022)
Periodontitis has been demonstrated to be bidirectionally associated with diabetes and has been recognized as a complication of diabetes. As a periodontal pathogen, Porphyromonas gingivalis is a possible pathogen linking periodontal disease and systemic diseases. It has also been found to be involved in the occurrence and development of diabetes. In this study, 6-week-old male C57BL/6 mice were orally administered the P. gingivalis strain ATCC381 for 22 weeks. Histological analysis of the gingival tissue and quantified analysis of alveolar bone loss were performed to evaluate periodontal destruction. Body weight, fasting glucose, glucose tolerance test (GTT), and insulin tolerance test (ITT) were used to evaluate glucose metabolism disorder. We then analyzed the expression profiles of inflammatory cytokines and chemokines in gingival tissue, the liver, and adipose tissue, as well as in serum. The results showed that mice in the P. gingivalis-administered group developed apparent gingival inflammation and more alveolar bone loss compared to the control group. After 22 weeks of P. gingivalis infection, significant differences were observed at 30 and 60 min for the GTT and at 15 min for the ITT. P. gingivalis-administered mice showed an increase in the mRNA expression levels of the pro-inflammatory cytokines (TNF-α, IL-6, IL-17, and IL-23) and chemokines (CCL2, CCL8, and CXCL10) in the gingiva and serum. The expression levels of the glucose metabolism-related genes were also changed in the liver and adipose tissue. Our results indicate that oral administration of P. gingivalis can induce changes in the inflammatory cytokines and chemokines in the gingiva and blood, can lead to alveolar bone loss and to inflammatory changes in the liver and adipose tissues, and can promote glucose metabolism disorder in mice.